Synergistic effect of Fe and Co doped ZnO nanoparticles synthesized using Alpinia galanga against Candida parasilopsis - Narendhran S (Zaštita Materijala)
In this investigation, nanoparticles such as ZnO, Fe doped ZnO and Co doped ZnO NPs prepared by the co-precipitation method were tested against the pathogenic yeast. The spectroscopic analyses were carried out to identify the morphological and chemical composition of the synthesized nanoparticles. The results of XRD analysis revealed that the synthesized nanoparticles were crystalline in nature with average size ranges between 32 – 34 nm approximately. EDX and SEM analysis were carried out to identify the element composition (Co, Fe and Zn) and spherical shape of nanoparticles. The functional group that is responsible for the capping and stability of nanoparticles was confirmed by FTIR analysis,  to compare the antifungal efficiency of ZnO, Fe doped ZnO and Co doped ZnO from the resultant zone of inhibition.